Cameron Douglas: capstone - Douglas, Cameron, artist (Colorado State University. Libraries, 2023)
The artist's statement: As a graphic designer, I strive to push the boundaries of design by creating work which blends physical mark making with digital refinement. My background of print-making has allowed me to bring my work into the physical world in a variety of ways, ranging from screen printing to photo-lithography. Within my work I am passionate about creating the perfectly imperfect design. To me this defined as a design with a high level of a craftsmanship while leaving space for the material to breathe. I am inspired by the world around me, particularly urban and organic textures. My love for pulling my designs into the physical realm extents to the art directing aspect of documenting my work. In my previous body of work, Yard Sale, I designed and printed ski apparel. Then orchestrated a photo-shoot of athletes performing winter activities in my clothing. This set of photos was then applied to a full magazine, which highlighted the application of my photography in conjunction to my typographic ability. In addition to my hand craft prints, I also have experience working with clients designing and preparing branding material to be manufactured. Working with clients and other designers has create a new found appreciation for collaboration. Being able to bounce ideas of other others is my favorite part of the creative process. One of my most recent projects, African & Ale event t-shirts, was based in pure collaboration. The background our team ranged from art historians to graphic designers. Together we managed to blend our compositions into one cohesive design which remained culturally appropriate and communicating the concept of the event in a visually appealing way. My innate ability to consistently go above and beyond for clients has allowed me to carve a path for a successful design career. In addition to this my knowledge in production and print making sets me appart from others. Not only can I produce a strong body of work as an individual, I find most gratification in working with others. As a graphic designer I strive to make the world a better place through visual communication.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design